2013
DOI: 10.1002/rem.21371
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effective Sediment Dredge Disposal Options for Small Craft Harbors in Canada

Abstract: Sediment dredge disposal options were reviewed to improve cost‐effectiveness and environmental safety for dredging of coastal sediments at the Department of Fisheries and Oceans Small Craft Harbours (DFO‐SCH) program in Canada. Historically, contaminated dredge sediments exceeding federal guidelines were disposed of in nearby landfills. Recent federal regulatory changes in sediment quality guidelines adopted by provincial regulators in Canada has resulted in updates to guidelines for disposal of contaminated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Many of these divested harbors have legacy contaminant issues, with many requiring costly maintenance dredging and disposal of contaminated sediments (Walker et al, 2013e).…”
Section: Potential Future Harbour Management Issuesmentioning
confidence: 99%
“…Many of these divested harbors have legacy contaminant issues, with many requiring costly maintenance dredging and disposal of contaminated sediments (Walker et al, 2013e).…”
Section: Potential Future Harbour Management Issuesmentioning
confidence: 99%
“…Results Removal. Sediment dredge disposal options were reviewed in response to recent federal regulatory changes in sediment quality guidelines adopted by provincial regulators in Canada that has resulted in updates to guidelines for disposal of contaminated solids in landfills (Walker et al, 2013).…”
Section: Phytoremediationmentioning
confidence: 99%
“…SCHs in Nova Scotia are small water lots that support various fisheries industries and are managed by Fisheries and Oceans Canada-Small Craft Harbors (DFO-SCH). Previous studies have identified that PAHs and other contaminants are commonly present in detectable concentrations in sediments of Nova Scotia SCHs (Walker, MacLean, et al, 2013;Davis et al, 2018;Zhang et al, 2019).…”
mentioning
confidence: 99%